1996
DOI: 10.1073/pnas.93.22.12461
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of a recurrent V beta 5.3+ T-cell population in newly diagnosed and untreated HLA-DR2 multiple sclerosis patients.

Abstract: We have used a PCR-based technology to study the V185 and V1317 repertoire of T-cell populations in HLA-DR2 multiple sclerosis (MS) patients. We have found that the five MS DR2 patients studied present, at the moment of diagnosis and prior to any treatment, a marked expansion of a CD4+ T-cell population bearing Ve ¶35-J.81. The characterization of T cells involved in MS is crucial to the description of the disease. Several strategies have been used to identify possible biases in the T-cell repertoire of MS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…D, CDR-3 profiles for the predominately used rearrangement CHe-VH3b in omalizumab-treated patients. Whereas patient 2 showed virtually no changes in IgE and IgG repertoires, patients 13 and 7 showed broader profiles of their IgG transcripts, together with unchanged (13) or reduced (7) IgE repertoires for this rearrangement. IgM (with the exception of a single peak for patient 7) remained in a Gaussian-like distribution.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…D, CDR-3 profiles for the predominately used rearrangement CHe-VH3b in omalizumab-treated patients. Whereas patient 2 showed virtually no changes in IgE and IgG repertoires, patients 13 and 7 showed broader profiles of their IgG transcripts, together with unchanged (13) or reduced (7) IgE repertoires for this rearrangement. IgM (with the exception of a single peak for patient 7) remained in a Gaussian-like distribution.…”
Section: Discussionmentioning
confidence: 87%
“…12 In analogy to the T-cell receptor diversity, these rearrangements can be described as ''public'' in contrast to unique ''individual'' rearrangements. 13 Of interest, some studies showed a preferential rearrangement of the VH5 chain, 14-16 a variable chain that is used at low percentages for IgM and IgG clones. However, not all studies confirmed this preference.…”
mentioning
confidence: 99%
“…Differences in T-cell repertoire have been observed in other immune-mediated diseases, such as multiple sclerosis, 38,39 rheumatoid arthritis, 40,41 and autoimmune hepatitis, 42 where a limited number of T cells using a restricted diversity of the V ␤ subfamilies to proliferate dominantly is revealed in different patients, 21 but the TCR repertoire pattern is different among these diseases owing to the different antigenic triggers. 39,43,44 In summary, we show that in HAA there is an infiltration of both clonal and many nonclonal T cells, giving rise to a markedly skewed T-cell repertoire, as seen in both viral and autoimmune hepatitis. This highly skewed T-cell repertoire is also evident in the blood at the time of presentation of bone marrow failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, none has been established in vitro so far. On the human side, there is no evidence to date of monoclonal expansions of distinctive T cell clones in SLE [16], in distinction to what has been found in some other autoimmune diseases such as multiple sclerosis [17]. The lack of results in human SLE does not, however, entirely dismiss the T cell repertoire analysis approach and rather points to the need for better defining the cohorts to be studied.…”
Section: Introductionmentioning
confidence: 99%